Fungal resistance of nanomodifiers and corrosion inhibitor amended fly ash concrete. (September 2019) - Harilal, Manu; Uthaman, Sudha; Anandkumar, B.; Lahiri, B.B.; George, R.P.; Philip, John; Amarendra, G.
Abstract: In this paper, we report a novel concrete composition with enhanced biodeterioration resistance against colonization and fouling by fungus Fusarium oxysporum . The new formulation (CFNI) contains 56 wt% cement, 40 wt% fly ash, 1 wt% nano-TiO2, 1 wt% nano-CaCO3 and 2 wt% sodium nitrite based corrosion inhibitor. The CFNI specimen is found to have minimal reduction in pH, weight loss and dimensional changes after three months of exposure in the aggressive fungal culture. Microscopic investigations confirmed the least biofilm thickness and minimum orange-red fluorescence intensity indicating lesser metabolizing cells on CFNI surface as compared to control concrete (CC). The distinct and compact calcium silicate hydrate (CSH) dominated surface morphology of CFNI specimen indicate the formation of more cementitious products with improved biodeterioration resistance. The nearly uniform phase intensity and faster temperature decay rate, seen in the infrared thermal images, confirm the absence of sub-surface micro-cracks, pores, and voids, and homogeneous thermal properties due to reduced biodeterioration of CFNI. These results suggest that a combination of nanomodifiers and corrosion inhibitor enable improved resistance against acid producing fungi attack on fly ash concrete. Highlights: A novel biodeterioration resistant HPGC was developed by the combination of cement, fly ash, nanoparticles and inhibitor. The antifungal activity of the new surface was demonstrated using advanced microscopic techniques. Minimal reduction in pH, weight and dimensional variations, distinct and compact surface morphology. Absence of sub-surface micro-cracks on the specimens confirmed enhanced biodeterioration resistance. The synergy between the nanomodifiers and inhibitor enabled resistance against fungi attack.